KOLABORASI TATA KELOLA KAMPUNG PELANGI KOTA SURABAYA - Indira Arundinasari (Halu Oleo University, 2022)
The KOTAKU program was adopted by the Surabaya City Government through the arrangement of fishing villages. In structuring this village, the Surabaya City Government cooperates with the private sector and community participation to build a village that was originally a slum into a village that has art, characteristics and tourism selling values. This village is called Kampung Pelangi. This study uses a qualitative approach and data analysis techniques according to Miles Huberman and Sandana by reducing, presenting data and drawing conclusions. This study uses the theory of Collaborative Governance Anshell and Gash, initial conditions, institutional design, facilitative leadership, and collaborative processes. The results of this study indicate that the collaboration process between stakeholders is effective. The result of this collaborative governance is the creation of Kampung Pelangi as a new tourist destination in the city of Surabaya.